Efficacy of Clonal Propagation in Andaman Padauk (Pterocarpus dalbergioides): Augmenting Conservation of an Endemic Ornamental Timber Species of Andaman & Nicobar Islands, India. Issue 5 (16th August 2021) - Jaisankar, Iyyappan; Varadan, R Jayakumara; Vijayakumar, S; Jambhulkar, Nitiprasad Namdeorao; Jerard, Bosco Augustine; Ganguly, Nabanita; Rajkumar, Muthu; Moses, Ezekiel Manasseh; Simhachalam, Putcha
Abstract: The population of Andaman padauk ( Pterocarpus dalbergioides Roxb.), an endemic ornamental timber species, is fast depleting in the Andaman Islands. Afforestation through seedlings is hindered by low germination and high mortality rates. This study attempts to assess the efficacy of clonal propagation methods to hasten mass multiplication by trying out different combinations of growth hormones, concentration, and dipping duration in semi-hardwood stem cuttings and different combinations of growth hormone concentration and substrate in air layering. Dipping the cuttings in indole-3-butyric acid (IBA) 1, 500 ppm for 24 hours and spraying the modified stem-cut layers with IBA 2, 000 ppm and binding with top soil and decomposed coir dust turned out to be the best treatment combination for cutting and air layering, respectively. Among the considered factors, the concentration of growth hormone is crucial for cutting, as the performance is enhanced with concentration under a given growth hormone and dipping duration. Similarly, the substrate is crucial for air layering, as modified stem-cut air layers bound with top soil and decomposed coir dust not only achieve the best performance, but also catalyze IBA for further improvement when other substrates remain unresponsive. Successful outcome of both clonal propagation techniques gives hope for disseminating the species across the tropics at global level.